The Relevance of Michael J. Losier’s Law of Attraction Theory to Sufism of Al-Ghazālī - Hafil, Ach. Shodiqil; Rahmawati, Desty (Proceedings of International Conference on Muslim Society and Thought, 2024)
This article is motivated by the rise of the Law of Attraction content on social media. The law of Attraction is a concept that states that positive thoughts will attract positive reality, and vice versa. Not only popular in Western culture, the Law of Attraction also interests Indonesians with the claim that one can change their destiny with just a thought. Although the Law of Attraction is not specifically mentioned in Islamic literature, the author tries to identify this concept in the concept of Islamic teachings, namely in Al-Ghazālī’s Sufism which is known to be oriented towards moral improvement. This article uses descriptive-analytical qualitative research. The relevance of the Law of Attraction to Al-Ghazālī’s Sufism is related to the practice of the Law of Attraction according to Micahel J. Losier. The practice of the Law of Attraction shows Islamic values related to saving actions, namely tafakur, niyat, husnuzan, and tawakal.